Full synthesis and bioactivity evaluation of Tn-RC-529 derivative conjugates as self-adjuvanting cancer vaccines - Gao, Lingqiang; Lian, Qinghai; Ma, Leilei; Su, Shiwei; Yang, Menglan; Fang, Yuan; Liu, Zhongqiu; Luo, Xiang; Liao, Guochao (Chinese chemical letters, 2021)
Tn-based vaccines carried by RC-529 derivatives were synthesized and elicited strongly T cell-dependent immune responses without external adjuvants. The antisera induced by these conjugates could specifically recognize, bind to and kill Tn-overexpressing cancer cells. [Display omitted] A facile and efficient strategy was established for the construction of RC-529 and its derivatives. Four conjugates of RC-529 derivatives with Tn antigen were synthesized and all elicited strong and T cell-dependent immune responses in mice without requiring external adjuvants. In addition, all antisera induced by these conjugates could specifically recognize, bind to and kill Tn-overexpressing cancer cells. Thus, RC-529 shows promise as a useful platform for the development of new vaccine carriers with self-adjuvanting properties for the treatment of cancer. Moreover, preliminary structure-activity relationship analysis provides convincing support for further optimization of, and additional investigation into, RC-529.